Hedging In The Book of Proverbs of The Holy Bible - Erikson Togatorop (Politeknik Negeri Batam, 2012)
For some reasons and purpose, being realized or not, almost all writers use hedging in their writing. Hedging is widely used not only in secular but also in spiritual writing. This study is intended to investigate the use of hedging in one of the Holy Bible books, that’s the Book of Proverbs, which was believed written by King Solomon, the wisest king of Israel in about in about 970-930 BC. Using a qualitative method, the study found there are eight types of hedges occurred in the Book. From the most to the least frequent, they are: modal auxiliary 85 times (62.50%), agentless passive 33 times (24.26%), full verbs 7 times (5.15%), conditional sentences 3 times (2.21%), adjective twice (1.47%), noun and passive infinitives each once (0.74%)